The language of Uzbek films of the independence period in the mirror of morphological standards - Shirinova, Mexrigiyo (FILOLOGIYA UFQLARI JURNALI, 2024)
In the article, the language of some Uzbek films shot during the period of independence was selected as a research object and examined from the aspect of morphological norms. During the inspection, it was found that the language of the films also needs to be checked in terms of morphological standards. Both normative and non-normative cases of morphological means were observed in the language of motion pictures. The conclusions based on the observations were presented in diagrams and tables. It was noted that the morphological norm, like other literary language norms, is important in the formation and development of any literary language. It was proven based on examples that the language of movies plays a leading role in this. Conclusions were given that the future elimination of the shortcomings indicated in the examples can contribute to the development of literary language. Keywords: literary language, film language, literary standard, morphological standard, word builders, lexical form builders, syntactic form builders.